Entrepreneurship Education Management To Overcome The Intellectual Unemployment At Dzikir Al-Fath Sukabumi Islamic Boarding School - Ruswandi, Yudi; Gintings, Abdorrakhman; Koswara, Nandang (Advances in Social Sciences Research Journal, 2020)
This research was motivated by two facts in the field, namely: a) the data of job seekers who made the Kartu Kuning (Job Seeker Card) to Sukabumi City and Regional Office of Manpower and Transmigration reached 3,000 to 5,000 people; b) Unemployment rate in 2017 based on data from the Central Statistics Agency (BPS) in Sukabumi Regency reached 7.66% and Sukabumi City 8.00%. The purpose of this study is to describe the implementation of entrepreneurship education management and to uncover the success of the Al-Fath Sukabumi Islamic Boarding School in educating students to become entrepreneurs who have a vision of Islamic economics. Research procedures include pre-field activities, fieldwork, and data analysis. Data collection techniques consist of interviews, observation, and documentation study. The results of this study found that the application of entrepreneurship education management implemented in an integrated and comprehensive manner through the Lecture, Santri program, while Continuing Work Outsourcing (KSB2Osc). Based on these results, the conclusion of this study is that the Dzikir Al-Fath Sukabumi Islamic boarding school has succeeded in producing entrepreneurs who have a vision of Islamic economics. The success of the Dzikir Al-Fath Sukabumi Islamic Boarding School had an impact on the making the welfare of the people to be better. In accordance with the results of the study, the recommendations of this study are, first, other boarding schools can implement entrepreneurship education management so that more and more entrepreneurs have a vision of Islamic economics. Second, in relation with the development of E-Commerce, the Dzikir Al-Fath Islamic Boarding School has not reached development up to that point. This means that, in the future, E-Commerce must be part of the curriculum.